Perioperative management of adult living donor liver transplantation: Part 1 – recipients. Issue 6 (24th April 2022) - Sakai, Tetsuro; Ko, Justin Sangwook; Crouch, Cara E.; Kumar, Sathish; Little, Michael B.; Chae, Min Suk; Ganoza, Armando; Gómez‐Salinas, Luis; Humar, Abhi; Kim, Sang Hyun; Koo, Bon‐Nyeo; Rodriguez, Gonzalo; et al.
Abstract: Living donor liver transplantation was first developed to mitigate the limited access to deceased donor organs in Asia in the 1990s. This alternative liver transplantation option has become an established and widely practiced transplantation method for adult patients suffering from end‐stage liver disease. It has successfully addressed the shortage of deceased donors. The Society for the Advancement of Transplant Anesthesia and the Korean Society of Transplant Anesthesia jointly reviewed published studies on the perioperative management of live donor liver transplant recipients. The review aims to offer transplant anesthesiologists and critical care physicians a comprehensive overview of the perioperative management of adult live liver transplantation recipients. We feature the status, outcomes, surgical procedure, portal venous decompression, anesthetic management, prevention of acute kidney injury, avoidance of blood transfusion, monitoring and therapeutic strategies of hemodynamic derangements, and Enhanced Recovery After Surgery protocols for liver transplant recipients.